COMPARISON BETWEEN CONCENTRATED BONE MARROW ASPIRATE AND CORTICOID IN GLUTEAL TENDINOPATHY - Veiga Rosario, Davi Araujo [UNESP]; Faleiro, Thiago Batista; Ferreira Mendes Franco, Bruno Adelmo; Daltro, Gildasio De Cerqueira; Marchetto, Reinaldo [UNESP] (Atha Comunicacao & Editora, 2021)
Objective: To compare bone marrow aspirate concentrate (BMAC) with the standard treatment for gluteal tendinopathies. Methods: 48 patients diagnosed with gluteal tendinopathy at a university hospital were selected by a randomized clinical trial and divided into two groups: (G1) bone marrow aspirate concentrate and (G2) corticosteroid injections. Results: 40 of the 48 selected patients were monitored for six months and both groups showed better scores. Visual analog scale (VAS) scores and Lequesne index were statistically significant higher in patients submitted to BMAC treatment when compared to standard treatment. Both groups improved their quality of life, without statistically significant difference. Conclusion: BMAC constitutes an alternative to gluteal tendinopathy standard treatment, proving to be a safe technique with promising results when combined with multidisciplinary team behavioral therapy.
Keywords: Tendinopathy; Bone Marrow Cells; Hip Join; Adrenal Cortex Hormones